Analisis Bibliometrik Untuk Mengkaji Penerapan Digital Marketing Pada UMKM - Kartika Wati, Setiani; Kurniawati Widodo, Erry (SMARTINDO, 2024)
This paper aims to provide an overview and existing knowledge of digital marketing, which is applied to Small and Medium Micro Enterprises (MSMEs). The study used bibliometric analysis methods. Data were obtained through a Google Scholar (GS) database search with the word Digital Marketing at MSMEs as Article Title, Abstract, Keywords. About 200 articles were obtained in preliminary results with 143102 citations (14310.20 quotes/year). The search results obtained 138 articles, as well as the citation data changed, with 74904 citations and 7490.40 citations/year, during the period 2013-2023. From the results, 138 articles were refined and the citation data was also changed to 74904 citations and 7490.40 citations each year. The results show that the most cited authors are A. D. Teece, Margaret Peteraf, and Sohvi Leih published in journals.sagebup.com b. Zhao Huang and Morad Benyoucef are the most cited authors, Elsevier is the largest publisher crequent words are smes,, medium sized enterprise, marketing, and digital marketing. Bibliometric analysis supports scientific explanations between probability theory and evidence. Research on Digital Marketing in MSMEs can be developed more widely on themes that appear few and have not been included much in research in the last ten years. Therefore, this study is expected to serve as a reference for further research.